Perkembangan Pembuatan Perahu Sandeq Nelayan Suku Mandar Di Desa Pulau Kerasian, Kecamatan Pulau Laut Kepulauan, Kabupaten Kotabaru Tahun 1990-2012 - Bahri, Alim; Anis, Mohamad Zaenal Arifin; Syaharuddin, Syaharuddin (Lambung Mangkurat University, 2024)
The Mandar ethnic group is the only maritime tribe in the Archipelago that geographically faces the sea directly. For the Mandar people, boats are crucial to their way of life, serving not only as a means of transportation but also as their livelihood source. The motorization of traditional sandeq boats among Mandar fishermen in Kotabaru Regency began in the 1990s. The development of motorized fishing boats in fishing villages in Kotabaru Regency is an intriguing subject of study. The research method employed in this study is historical research. In this method, the author applies systematic rules to gather data. Historical research involves four integral steps: heuristics, source criticism, interpretation, and historiography. Based on the research findings, it can be concluded that the development of motorized sandeq boats among Mandar fishermen in Pula Kerasian Village from 1980 to 1989, in general, did not involve motorized boats. This was because the fishermen in Kotabaru Regency had not yet been influenced by motorization during that period. However, in the 1990s, there was an increase in the use of motorized boats among fishermen in Kotabaru Regency due to the influence of motorization. From 2000 to 2010, there was a significant surge in the use of motorized boats, which was a direct impact of motorization. Fishermen in Kotabaru Regency preferred motor engines for sea travel for various reasons, such as their effectiveness compared to sailboats, which depend on wind propulsion.